2006
DOI: 10.1093/humupd/dml049
|View full text |Cite
|
Sign up to set email alerts
|

Mid-trimester induced abortion: a review

Abstract: Mid-trimester abortion constitutes 10-15% of all induced abortion. The aim of this article is to provide a review of the current literature of mid-trimester methods of abortion with respect to efficacy, side effects and acceptability. There have been continuing efforts to improve the abortion technology in terms of effectiveness, technical ease of performance, acceptability and reduction of side effects and complications. During the last decade, medical methods for mid-trimester induced abortion have shown a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
136
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 122 publications
2
136
1
Order By: Relevance
“…[12][13][14][15][16] For second trimester abortion (13-24 weeks of gestation), medical abortion with mifepristone followed by a prostaglandin analogue is an appropriate method and has been shown to be safe and effective, according to WHO and the RCOG. [17][18][19][20][21][22] It has been well proven that pretreatment with mifepristone 24-48 hours before prostaglandin administration increases the success rate, shortens the induction-to-abortion interval and reduces the amount of prostaglandins required in the second trimester in unscarred uteri. 23,24 In our series women with previous LSCS ,mifepristone 200 mg was given 36 hours prior to the misoprostol or oxytocin and found that none of the cases had incomplete abortion or rupture probably because we had ensured improvement in Bishop's score even by putting Foley's bulb before administration of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] For second trimester abortion (13-24 weeks of gestation), medical abortion with mifepristone followed by a prostaglandin analogue is an appropriate method and has been shown to be safe and effective, according to WHO and the RCOG. [17][18][19][20][21][22] It has been well proven that pretreatment with mifepristone 24-48 hours before prostaglandin administration increases the success rate, shortens the induction-to-abortion interval and reduces the amount of prostaglandins required in the second trimester in unscarred uteri. 23,24 In our series women with previous LSCS ,mifepristone 200 mg was given 36 hours prior to the misoprostol or oxytocin and found that none of the cases had incomplete abortion or rupture probably because we had ensured improvement in Bishop's score even by putting Foley's bulb before administration of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…3 The regimen that has been most widely studied 4 involves administering mifepristone 200 mg orally on an outpatient basis, followed 36-48 hours later by admission to the clinic or hospital and administration of misoprostol 800 mcg vaginally. The woman is then given further doses of misoprostol 400 mcg orally as necessary, every three hours, until abortion occurs, to a maximum of four doses.…”
mentioning
confidence: 99%
“…Different studies have shown success rates varying from 73-97% with combination of mifepristone and misoprostol. 16,17,18 The mean doses of misoprostol required in group 1 was 1081.48 µg. Other studies found dosage requirements varying from nil to 2200 µg.…”
Section: Discussionmentioning
confidence: 99%